2021
DOI: 10.1177/23197145211042521
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Support and Intention to Stay: The Mediating Effect of Employee Engagement

Abstract: The present study intends to investigate the influence of perceived organizational support (POS) on employee intention to stay (ITS) in an organization. Further, study examines the mediating role of employee engagement (EE) on the relationship between perceived organizational support (POS) and employee intention to stay (ITS). Data has been collected from 323 employees working in three major private telecom companies, namely, Airtel Limited, Vodafone–Idea Limited and Reliance Jio Infocomm Limited operating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…This aligns with the principles of social exchange theory, wherein employees reciprocate the support and care extended by their organization through heightened commitment and a reduced desire to quit. This finding corroborates previous research (e.g., Jing & Yan, 2022;Nargotra & Sarangal, 2023) that has consistently demonstrated the mitigating effect of organizational support on turnover intentions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This aligns with the principles of social exchange theory, wherein employees reciprocate the support and care extended by their organization through heightened commitment and a reduced desire to quit. This finding corroborates previous research (e.g., Jing & Yan, 2022;Nargotra & Sarangal, 2023) that has consistently demonstrated the mitigating effect of organizational support on turnover intentions.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have corroborated that there is a positive relationship between perceived organizational support and job satisfaction. Furthermore, job satisfaction plays a significant role in influencing an employee's intention to remain with the organization, effectively reducing turnover intention (Jing & Yan, 2022;Maertz & et al, 2007;Nargotra & Sarangal, 2023). Highly committed employees tend to have longer tenures because they perceive that the organization cares about their well-being.…”
Section: Relationship Between Perceived Organizational Support and Tu...mentioning
confidence: 99%
“…According to research by Soomro et al, (2023) in the banking sector, which examines perceived organizational support, employee engagement, and employee retention, the results showed that companies with a strong organizational support system could maintain and retain their employees over a long period. These findings were from a study conducted by Nargotra & Sarangal, (2023), which showed that perceived organizational support has a significant positive impact on survival intention and employee engagement, where employee engagement was partly a mediator in the relationship between perceived organizational support and survival intention.…”
Section: Introductionmentioning
confidence: 88%
“…When employees are satisfied with their leaders in an organization, it can have a favorable impact on their levels of engagement, loyalty, and their willingness to stay with the organization (Book et al, 2019). The way employees perceive the assistance provided by their organization has a beneficial impact on their intention to stay with the company, as mediated by a certain level of employee engagement (Nargotra & Sarangal, 2023;Suhendra, 2021).…”
Section: Employee Engagementmentioning
confidence: 99%